Using blogging to promote clinical reasoning and metacognition in undergraduate physiotherapy fieldwork programs - Tan, S.; Ladyshewsky, Richard; Gardner, Peter (Australasian Society for Computers in Learning in Tertiary Education &Australian Society for Educational Technology, 2010)
This qualitative study investigated the impact of using blogs on the clinical reasoning and meta-cognitive skills of undergraduate physiotherapy students in a fieldwork education program. A blog is a web based document that enables individuals to enter comments and read each others' comments in a dynamic and interactive manner. In this study, final year physiotherapy students were randomly allocated to group blogs to share their reflections on their own and their peers' clinical practice. Blogging was used to help students reflect and focus on professional and evidence based practice within a supportive peer assisted learning environment. The text within each of the blogs was qualitatively analysed against concepts in the literature describing specific types of clinical reasoning and metacognition. A range of clinical reasoning typologies were found to exist in the blogs. Most notable were ethical, interactive and procedural reasoning along with evidence of metacognition. Blogging was found to be a good strategy for promoting clinical reasoning and metacognition in fieldwork education.